2013
DOI: 10.1111/jocd.12027
|View full text |Cite
|
Sign up to set email alerts
|

Reductions in body measurements promoted by a garment containing ceramic nanoparticles: a 4‐month follow‐up study

Abstract: The experimental data showed that the occlusive treatment with a garment composed of ceramic particles promoted reductions in body measurements during a 120-day experimental period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The thermal effect within deep tissues can expand the blood vessels and promote blood microcirculation to eliminate metabolic toxins and waste [6,7]. Therefore, FIR textiles are always considered as an integration of therapeutic and thermal-protective segments, which have been widely used for various kinds of healthcare applications, such as warmth retention [8,9,10], relief from inflammation [11,12], wound healing [13,14], weight loss [15,16] and relief from aching pains [17,18]. Similarly, considering its physical therapy efficacy, the general requirements for FIR products in European and American countries are to assess a subjects’ blood oxygen content and flow velocity through a human wear trial over weeks or months.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal effect within deep tissues can expand the blood vessels and promote blood microcirculation to eliminate metabolic toxins and waste [6,7]. Therefore, FIR textiles are always considered as an integration of therapeutic and thermal-protective segments, which have been widely used for various kinds of healthcare applications, such as warmth retention [8,9,10], relief from inflammation [11,12], wound healing [13,14], weight loss [15,16] and relief from aching pains [17,18]. Similarly, considering its physical therapy efficacy, the general requirements for FIR products in European and American countries are to assess a subjects’ blood oxygen content and flow velocity through a human wear trial over weeks or months.…”
Section: Introductionmentioning
confidence: 99%
“…Three clinical studies have reported that blood flow was increased by infrared exposure from powered IR sources or non-powered ceramics [ 2 , 22 , 23 ] and one clinical study found alleviation of the symptoms of Raynaud's syndrome with ceramic impregnated gloves [ 24 ]. Other clinical studies with topically applied ceramic materials have demonstrated changes in body measurements (fat loss) [ 25 , 26 ], reduced dysmenorrhea [ 27 ], and improved lactation [ 28 ].…”
Section: Discussionmentioning
confidence: 99%